Implementasi Model Penilaian Produk Dalam Pembelajaran Matematika Berbasis Lesson Study di SMP Muhammadiyah 1 Kartasura - Puspanti, Vella Ananditya (2016)
The purpose of this study is to determine: (1) teacher at SMP Muhammadiyah 1 Kartasura already understand about the product assessment, (2) the implementation process model of product assessment in mathematics-based lesson study, (3) the constraints that faced in implementing the model product assessment. This research is qualitative research. Are more descriptive qualitative research, the data collected is in the form of words, pictures, and not numbers. It can be concluded that: (1) teacher at SMP Muhammadiyah 1 Kartasura not understand clearly the product assessment, (2) the implementation process model of product assessment in mathematics-based lesson study is at the stage of plan making device product assessment and the lesson study, stage do teachers make the learning process according RPP, stage see done in the form of a discussion that followed the entire working group lesson study, using the product assessment can increase the liveliness of the discussion and the courage to ask questions, so that the average post test of students has increased, (3) the constraints teachers face in implementing the valuation model is the product during manufacture student worksheets and scoring rubric manufacture products.